Building of the Pancasila Character with Religious Harmony in the Globalization Era - Ahmad Hariyadi; Jenuri Jenuri; Didit Darmawan; Dina Mayadiana Suwarma; Susatyo Adhi Pramono (STAI Hubbulwathan Duri, 2023)
Globalization is a global condition where change is shown and has a good or even bad impact on its users. They grew up with all the digital conveniences at their fingertips. Today's youth are privileged to grow up in a digitally advanced and globally connected world. However, a moral dilemma does hit the millennial generation in the classroom. The moral deviations indicated that many of the younger generations do not have good character in themselves. This research case illustrates why this research is worth discussing. This research contributes to a generation of young people who are characterized and civilized according to Islamic values and the values of Pancasila (citizenship). In this study, data collection used a qualitative approach with a literature review approach: reading journals, articles, or books as research data. The findings in this research (a) the nation's youth need to have full awareness to encourage themselves to take ethical values that combine knowledge, understanding, and action to create a comprehensive character. (b) the best practice in the formation of the Pancasila character is implementing and applying what is received so that it becomes a habit of attitude/behaviour in the life of the nation and state. (c) the values of Pancasila are contributed by Islamic religious education as a construction for the formation of a young generation with character, global outlook, love of the motherland, and the spirit of Pancasila in order of religious harmony. Limitations in this study only focus on discuss the prospects and challenges of character building in the midst of the globalization era, the best practices in character building in terms of Religious character and Pancasila, and the relevance of Islamic religious education and Pancasila values